The effect of situational norms on stigmatization of ex-offenders - Wong, Wei Jin (2018)
Stigmatization affects the successful reintegration of ex-offenders back to society. This study thus seeks to find out if situational norms (loose or tight) can affect the level of stigmatization people feel toward ex-offenders. It is hypothesized that participants in the loose condition would show less stigmatizing views toward ex-offenders compared to those in the tight condition. A prime image (hotel room or job interview) was used to activate participants’ situational norms of the situation portrayed and were shown individually to 88 undergraduate participants (44 males, 43 females). Participants’ ratings of the tightness or looseness of the situation, as well as the strength of the norms and tolerance for deviance were measured. Measures of crime attribution, perceived severity of crime, feelings toward the ex-offender, as well as desired social distance were also used to measure for stigmatizing attitudes. Results showed that participants displayed significant differences in their ratings of the tightness-looseness of the situations, and those in the loose condition showed significantly less attribution of the crime to the ex-offender and less perceived severity of the crime committed. However, no significant differences were observed in their feelings toward the ex-offender or desired social distance from the ex-offender between the two conditions. It is suggested that this mixed support for the hypothesis could be due to age, cultural, and gender limitations of the participants or could also be explained by the Theory of Planned Behaviour.